Software quality : the complexity and challenges of software engineering and software quality in the cloud : 11th International Conference, SWQD 2019, Vienna, Austria, January 15-18, 2019, Proceedings /: the complexity and challenges of software engineering and software quality in the cloud : 11th International Conference, SWQD 2019, Vienna, Austria, January 15-18, 2019, Proceedings. (2019) - Unknown
No abstract available